The Effects of Meditation, Yoga, and Mindfulness on Depression, Anxiety, and Stress in Tertiary Education Students: A Meta-Analysis - Breedvelt, Josefien J. F.; Amanvermez, Yagmur; Harrer, Mathias; Karyotaki, Eirini; Gilbody, Simon; Bockting, Claudi L. H.; Cuijpers, Pim; Ebert, David D. (Frontiers in Psychiatry, 2019)
Abstract Background Meditation, yoga, and mindfulness are popular interventions at universities and tertiary education institutes to improve mental health. However, the effects on depression, anxiety, and stress are unclear. This study assessed the effectiveness of meditation, yoga, and mindfulness on symptoms of depression, anxiety, and stress in tertiary education students. Methods We searched Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, PsycINFO and identified 11.936 articles. After retrieving 181 papers for full-text screening, 24 randomized controlled trials were included in the qualitative analysis. We conducted a random- effects meta-analysis amongst 23 studies with 1373 participants. Results At post-test, after exclusion of outliers, effect sizes for depression, g = 0.42 (95% CI: 0.16 - 0.69), anxiety g = 0.46 (95% CI: 0.34 - 0.59), stress g = 0.42 (95% CI: 0.27 - 0.57) were moderate. Heterogeneity was low (I2 = 6%). When compared to active control, the effect decreased to g = 0.13 (95% CI: -0.18 - 0.43). No RCT reported on safety, only two studies reported on academic achievement, most studies had a high risk of bias. Conclusions Most studies were of poor quality and results should be interpreted with caution. Overall moderate effects were found which decreased substantially when interventions were compared to active control. It is unclear whether meditation, yoga or mindfulness affect academic achievement or affect have any negative side effects.